2016
DOI: 10.1016/j.jngse.2016.08.061
|View full text |Cite
|
Sign up to set email alerts
|

A new method to determine Biot's coefficients of Bakken samples

Abstract: In recent years, the development of oil and gas from shale has proceeded quickly in the world through the use of multistage fracturing technology in horizontal well. However, without the knowledge of rock poroelastic characteristics, the successful rate of hydraulic fracturing will be low. Among those poroelastic characteristics, effective stress is required for creating artificial fractures in the shale formation. In this study a new method is proposed to measure the Biot"s coefficient, which is one of the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Such findings also have implications for petrophysics studies where the poroelastic constants are used to assist in the evaluation of petrophysical parameters (Shafer, Boitnott, and Ewy 2008;Schutjens and Heidug 2012). Another perspective comes from the geomechanics community where the effective stress principle is applied over and over and where measurements of the corresponding effective stress coefficients are often carried out (e.g., Lion, Skoczylas, and Ledesert 2004;Sulem and Ouffroukh 2006;Jaeger, Cook, and Zimmerman 2007;Omdal et al, 2009;He and Ling 2014). Of particular interest is the effective stress coefficient for the bulk volume which in the Biot framework is called the Biot coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings also have implications for petrophysics studies where the poroelastic constants are used to assist in the evaluation of petrophysical parameters (Shafer, Boitnott, and Ewy 2008;Schutjens and Heidug 2012). Another perspective comes from the geomechanics community where the effective stress principle is applied over and over and where measurements of the corresponding effective stress coefficients are often carried out (e.g., Lion, Skoczylas, and Ledesert 2004;Sulem and Ouffroukh 2006;Jaeger, Cook, and Zimmerman 2007;Omdal et al, 2009;He and Ling 2014). Of particular interest is the effective stress coefficient for the bulk volume which in the Biot framework is called the Biot coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned publications [8][9][10] may be listed as examples (although certainly not exhaustive for the topic), these being core works aimed at giving a precise definition of terminology and research methodology. The following publications are similar in nature: [22], which includes a thorough analysis of the variability of Biot coefficient for various types of sandstone and limestone, and [23], which verified the method for determining Biot coefficient, previously proposed in [24]. Materials published by the American Rock Mechanics Association in 2013 include the work [25], related to phenomena occurring in rock during liquid saturation and pore pressure induction, as well as the paper [26] concerning the influence of the pore pressure on the value of Biot coefficient, and as a result, on the form of the effective pressure rule.…”
Section: Materials Identification-constitutive Equation Of the Mediummentioning
confidence: 67%
“…Ref. [27] conducted a set of laboratory experiments on shale rocks with different porosity and confining pressure. They found that shale rocks show a very changeable Biot coefficient in different values of porosity and confining pressure.…”
Section: Discussionmentioning
confidence: 99%